Audio description as an accessibility enhancer - Martins, Cláudia (2013)
Audio description for the blind and visually-impaired has been around since people have described what is seen. Throughout time, it has evolved and developed in different contexts, starting with daily life, moving into the cinema and television, then across other performing arts, museums and galleries, historical sites and public places. Audio description is above all an issue of accessibility and of providing visually-impaired people with the same rights to have access to culture, education and ultimately social life. It has to do with making them feel part of society